2014
DOI: 10.1002/chem.201404775
|View full text |Cite
|
Sign up to set email alerts
|

Lead Structures for New Antibacterials: Stereocontrolled Synthesis of a Bioactive Muraymycin Analogue

Abstract: Naturally occurring muraymycin nucleoside antibiotics represent a promising class of novel antibacterial agents. The structural complexity suggests the investigation of simplified analogues as potential lead structures, which can then be further optimized towards highly potent antimicrobials. Herein we report studies on muraymycin-derived potential lead structures lacking an aminoribose motif found in most naturally occurring muraymycins. We have identified a 5'-defunctionalized motif to be ideal in terms of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 39 publications
2
73
1
Order By: Relevance
“…To date, several derivatives of uridylpeptide natural products have been generated through engineering of the organisms that produce the natural products or through semi-synthetic approaches and, as such, feature limited structural variation171819202122232425. A number of synthetic studies have also been reported on uridylpeptide natural products and analogues2627282930313233, some of which have been shown to possess antimicrobial activity78. The focus of the present study was to develop a rapid and divergent synthetic strategy to access a diverse library of sansanmycin analogues that would enable the determination of key structure-activity relationships specifically against Mtb.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several derivatives of uridylpeptide natural products have been generated through engineering of the organisms that produce the natural products or through semi-synthetic approaches and, as such, feature limited structural variation171819202122232425. A number of synthetic studies have also been reported on uridylpeptide natural products and analogues2627282930313233, some of which have been shown to possess antimicrobial activity78. The focus of the present study was to develop a rapid and divergent synthetic strategy to access a diverse library of sansanmycin analogues that would enable the determination of key structure-activity relationships specifically against Mtb.…”
Section: Resultsmentioning
confidence: 99%
“…Through design of simplified analogues, the terminal urea dipeptide motif [40] as well as the 5 -O-aminoribosyl substituent [21,39] were identified to mediate key interactions in MraY inhibition. However, synthetically obtained 5 -defunctionalized ( 5 -deoxy') muraymycin C4 that was reported by our group [38] was found to still inhibit MraY in the nM range, even though most naturally occurring muramycins are MraY inhibitors with pM activities [39]. The replacement of (3S)-3-hydroxy-L-leucine with L-leucine resulted in a~25-fold loss of activity [41], but that implied that such simplified analogues may still be employed in SAR studies.…”
Section: Introductionmentioning
confidence: 91%
“…Total syntheses of some naturally occurring muraymycins have been reported though [13,[27][28][29], and synthetic routes towards crucial structural motifs have been developed [30][31][32][33]. Both for potential applications and for more straightforward SAR studies, several simplified muraymycin analogues have been designed [34][35][36][37][38]. By comparison of different natural products and synthetic analogues with long alkyl side chains, it was shown that increased lipophilicity improves antibacterial activities (MIC values), but has only a minor effect on MraY inhibition [17,20,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of ap rimary amine that would displace the metal in the actives ite, this strategy exploits as trategic carboxylica cid functionality to investigate if such compounds mighto ffer advantagesi nbinding by directly coordinating ab ound divalent cation at the active site. [39,40] Such as trategy would mimic the proposed mechanism of tunicamycin-like nucleosides, which are thought to intercept bindinga si llustrated in Figure 1. To this end, Fmoc-l-Asp(tBu)-OHw as coupled to compound 19,f ollowedb yF moc removal using 20 %p iperidine.…”
Section: Strategy 2-tunicamimeticsmentioning
confidence: 99%